2013
DOI: 10.1631/jzus.b1200034
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal status and associated risk factors among childbearing age women in Cixi City of China

Abstract: Abstract:Objective: To investigate the periodontal status and associated risk factors among women of childbearing age to increase the awareness of oral health. Methods: The study was conducted on childbearing age women in Cixi, a city in Zhejiang Province in the southeast of China. A total of 754 women participated in periodontal examination while receiving prenatal care. Data of the women were collected from the Cixi Family Planning Commission and during an interview. Clinical periodontal indices, such as ble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 33 publications
(37 reference statements)
2
30
0
Order By: Relevance
“…Also, we noticed a positive association of level of education of pregnant women and their periodontal health status ( P = 0.029) which is similar to the findings reported previously [12]. The rate of periodontitis, in our study, is slightly lower than that reported elsewhere probably due to study population comprising women of lower age group from middle and upper middle income category and nonsmokers [10, 12]. Many researchers reported higher detection rates of P. gingivalis , T. forsythia , P. intermedius , and T. denticola among patients with periodontitis [4, 13].…”
Section: Discussionsupporting
confidence: 91%
“…Also, we noticed a positive association of level of education of pregnant women and their periodontal health status ( P = 0.029) which is similar to the findings reported previously [12]. The rate of periodontitis, in our study, is slightly lower than that reported elsewhere probably due to study population comprising women of lower age group from middle and upper middle income category and nonsmokers [10, 12]. Many researchers reported higher detection rates of P. gingivalis , T. forsythia , P. intermedius , and T. denticola among patients with periodontitis [4, 13].…”
Section: Discussionsupporting
confidence: 91%
“…, Wu et al. ) were found to contribute to between‐study heterogeneity. The heterogeneity decreased to 33.4% ( P for heterogeneity = 0.101) and the pooled RR was 1.39 (95% CI 1.24–1.55) after excluding these three studies.…”
Section: Resultsmentioning
confidence: 99%
“…Two surveys indicated the rates of periodontal disease nearly 50% and 78% among pregnant women of Shanghai and Shenzhen, Guangdong China respectively [6, 26]. Another survey conducted among childbearing age women in Zhejiang Province, China showed the prevalence nearly 85% [27]. All these studies indicated the high prevalence of periodontal disease among Chinese women of childbearing age.…”
Section: Discussionmentioning
confidence: 99%
“…Periodontal disease has been reported to be more common in deprived or disadvantaged populations [9, 27]. Additional risk factors for periodontal disease include older age, Hispanic and non-Hispanic Black ethnicity, being overweight and obese, poor oral hygiene, more stressful psychological status, tobacco use, alcohol consumption, taking oral contraceptives, increased parity, gestational age, public dental insurance (versus private), and lacking a recent dental visit (within six months) [7, 9, 30, 31].…”
Section: Discussionmentioning
confidence: 99%